Transcriptome Analysis of Gills Provides Insights Into Translation Changes Under Hypoxic Stress and Reoxygenation in Golden Pompano, Trachinotus ovatus (Linnaeus 1758) - San, Lize; Liu, Baosuo; Liu, Bo; Guo, Huayang; Guo, Liang; Zhang, Nan; Zhu, Kecheng; Jiang, Shigui; Zhang, Dianchang (Frontiers in Marine Science, 2021)
Golden pompano (Trachinotus ovatus) is one of the most economically critical marine fish in South China. Low oxygen stress has resulted in substantial economic losses to the aquaculture of T. ovatus. However, the molecular responses of fish gills to hypoxia challenge remain unclear. To understand the mechanism underlying adaption to hypoxia, we analyzed the transcriptome of T. ovatus gills in response to hypoxic stress in the normal oxygen group, hypoxic group, and hypoxia treatment after oxygen recovery group. This study found that hypoxia for 8 h was the critical time of hypoxic stress and corresponded to the largest number of differentially expressed genes. After hypoxic stress, genes for chemokines, chemokine receptors, interleukins, complement factors, and other cytokines were significantly downregulated, which may be why fish are vulnerable to pathogen infection in a hypoxic environment. According to a Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, many downregulated genes were significantly enriched in the steroid biosynthesis, focal adhesion, and the extracellular matrix (ECM)-receptor interaction signal pathways, which affected cell signal transduction, adhesion, and apoptosis. Compared with the hypoxic group, the amounts of upregulated genes related to phagocytosis and protein degradation were upregulated in the dissolved oxygen recovery group. These results indicated that after the recovery of dissolved oxygen, the fish body repaired the stress-induced damage by rapidly removing misfolded proteins. These findings provide a better understanding of the hypoxia response mechanism of fish and represent a useful resource for the genetic breeding of T. ovatus.